Endocuff‐Assisted Colonoscopy for Identifying Sessile Serrated Polyps and Adenomas During Routine Colorectal Cancer Screening: A Retrospective Cohort Study - Ammad Javaid Chaudhary; Muhammad Saad Faisal; Abdullah Sohail; Hope Baldwin; Kevin Harris; Muhammad Shahzil; Muhammad Salman Faisal; Avi Toiv; Keith Mullins; Suraj Suresh (JGH Open)
ABSTRACT Background and Aims Polyps located in less accessible areas of the colon, such as inner curves of flexures, are often difficult to visualize. Colonoscope attachments such as the Endocuff have been developed to improve the visualization of these polyps. We aimed to assess the utility of Endocuff‐assisted colonoscopy (EAC) in the detection of tubular adenomas and sessile serrated polyps (SSP) compared to conventional colonoscopy during routine colorectal cancer screening. Patients and Methods This retrospective cohort study included patients who underwent colorectal cancer screening with either conventional colonoscopy or EAC between November 2022 and March 2023. The primary outcomes were SSP and tubular adenoma detection rates. Secondary outcomes included total procedure time, cecal intubation time, and ileal intubation rates. Results Of the 435 patients included, 189 (43%) underwent EAC, and 246 (57%) underwent conventional colonoscopy. The mean ± standard deviation number of polyps detected was 1.7 ± 2.2, the mean procedure time was 18.7 ± 7.5 min, and the mean cecal intubation time was 4.4 ± 3.3 min, with no significant differences between groups. A smaller proportion of patients in the EAC group had successful ileal intubation (14% vs. 55%; p < 0.01). The tubular adenoma detection rate was similar between EAC and conventional colonoscopy (41% vs. 39%; p = 0.70), but the SSP detection rate was significantly higher with EAC (16% vs. 8.5%; p < 0.01). Conclusion EAC may enhance the detection of difficult‐to‐visualize SSPs during screening colonoscopies without affecting overall procedure time. However, physicians should consider the examination indication when selecting EAC, as ileal intubation may be more challenging.